1986
DOI: 10.1073/pnas.83.12.4138
|View full text |Cite
|
Sign up to set email alerts
|

Purification to apparent homogeneity of a mu-type opioid receptor from rat brain.

Abstract: A mu-opioid-specific receptor was purified to apparent homogeneity from rat brain membranes by 6-succinylmorphine affinity chromatography, gel filtration, wheat germ agglutinin affinity chromatography, and isoelectric focusing. The purified receptor had a molecular weight of 58,000 as determined by NaDodSO4/polyacrylamide gel electrophoresis and was judged to be homogeneous by the following criteria: (i) a single band was detected by autoradiography after NaDodSO4/polyacrylamide gel electrophoresis of 125I-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…This hypothesis is not without precedent since it has recently been demonstrated that the/ztype opiate receptor binding site has an apparent molecular mass of 58 kDa [19,20]. In addition, we suggest that crosslinked, purified receptor binds SUPERFIT more efficiently than noncrosslinked receptor.…”
Section: Discussionmentioning
confidence: 72%
“…This hypothesis is not without precedent since it has recently been demonstrated that the/ztype opiate receptor binding site has an apparent molecular mass of 58 kDa [19,20]. In addition, we suggest that crosslinked, purified receptor binds SUPERFIT more efficiently than noncrosslinked receptor.…”
Section: Discussionmentioning
confidence: 72%
“…Opioid receptors have proven to be difficult to solubilize from cell membranes in a high-affinity, agonist-binding state. In most solubilization studies, the solubilized material was able to bind opiate alkaloids but failed to bind enkephalin peptides (Simonds et a!., 1980;Gioannini et al, 1985;Maneckjee et al, 1985;Cho et al, 1986;Ueda et a!., 1988;Li et al, 1992;Ofri et al, 1992). Furthermore, the solubilization process frequently resulted in the loss of guanine nucleotide influence on opioid agonist binding.…”
mentioning
confidence: 99%
“…K d can also be determined by measuring the amount of drug bound to the protein at different drug and lysate/protein concentrations. 24 In fact, receptors for the majority of known drugs were identified using this method, including adrenergic receptors 2527 , opioid receptors, 28, 29 cyclophilins, 30 and FKBP12. 31 In many of these studies, affinity chromatography was used side by side with binding assays as one of the purification steps.…”
Section: Target Identificationmentioning
confidence: 99%